The Novel “Ararat”: the Way to Salvation - Toumanian, Svetlana (Armenian Folia Anglistika, 2006)
The article aims at presenting the attempt of the translator of the novel Ararat by the American writer Elgin Groseclose to reproduce the interpretation of the key message of the novel. The author of the article tries to elucidate the answer to the question: what and who is saved when the world turns into Sodom and Gomorrah?